Po stronie kota. Wokół Wandy Borudzkiej - Kwiatkowska, Agnieszka (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
This article presents the life and works of Wanda Borudzka – a journalist, poet and author of children’s and young adult literature active in the interwar and postwar periods. Borudzka, an underrated author with modern viewpoints, was very actively pursuing women’s issues in the interwar period; she was also a pioneer of literary criticism of children’s and young adult literature and a nature lover sensitive to animals’ wellbeing. The key parts of her writings are pre-war journalism (especially opinion pieces published in women’s press), interest in folk culture (visible after World War II, especially in the collection Malowane domy [Painted houses]) and children’s poetry. A separate place among her literary works is occupied by the social realist young adult novel Dorota i jej towarzysze (Dorota and her companions). In Borudzka’s writings, animals play a significant role and particular attention is given to cats which often feature in her poems and have a special place both in Dorota’s heart, who was maliciously called “cat lady” by critics, and in the writer’s heart as well.